Menumbuhkan Karakter Kejujuran Melalui Pendidikan Dan Nilai-Nilai Pancasila Yang Luhur - Bagus Priambodo; Shinta Sari; Novi Priyono; Indah Cahyani Simare Mare; Ananda Silviandini; Pancagaluh Ratnasih (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
At this time honest behavior is very difficult to implement. Cheating, violating traffic regulations, corrupt behavior, are some of the actions that occur due to the loss of the value of honesty. Lying is just normal behavior. The Pancasila Education subject is a lesson that emphasizes honest behavior. Data collection techniques include direct observation, interviews with teachers and students, documentation in the form of images, and literacy based on relevant scientific articles. The research results show that the Pancasila Education subject has succeeded in forming students' honest character. Students' honest behavior is in line with the material content in this subject, namely values and norms. All educational institutions are obliged to actively participate in implementing an attitude of honesty from an early age so that the noble values of Pancasila are not eroded by modern developments.